2012
DOI: 10.6004/jnccn.2012.0064
|View full text |Cite
|
Sign up to set email alerts
|

Cancer- and Chemotherapy-Induced Anemia

Abstract: Anemia is prevalent in 30% to 90% of patients with cancer. Anemia can be corrected through either treating the underlying cause or providing supportive care through transfusion with packed red blood cells or administration of erythropoiesis-stimulating agents (ESAs), with or without iron supplementation. Recent studies showing detrimental health effects of ESAs sparked a series of FDA label revisions and a sea change in the perception of these once commonly used agents. In light of this, the NCCN Clinical Prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
186
0
20

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(206 citation statements)
references
References 80 publications
0
186
0
20
Order By: Relevance
“…Anemia may develop either by impaired function in red blood cell (RBC) production or because of renal tubular damage following treatment with cytotoxic drugs as a consequence of chemotherapy in patients with breast cancer (4). Moreover, reduced levels of erythropoietin negatively affects RBC production in bone marrow, inducing anemia; accordingly, cancer patients with anemia have been shown to present abnormal erythropoietin levels (5).…”
Section: Introductionmentioning
confidence: 99%
“…Anemia may develop either by impaired function in red blood cell (RBC) production or because of renal tubular damage following treatment with cytotoxic drugs as a consequence of chemotherapy in patients with breast cancer (4). Moreover, reduced levels of erythropoietin negatively affects RBC production in bone marrow, inducing anemia; accordingly, cancer patients with anemia have been shown to present abnormal erythropoietin levels (5).…”
Section: Introductionmentioning
confidence: 99%
“…However, Hb increments from baseline were moderately higher with the 2 FDA-approved regimens-weekly EA 40,000 U, and every 3 week DA 500 mcg-than with the extended dosing regimen. While the Hb response was fastest with the weekly EA regimen, it is unclear whether rapid Hb increment is beneficial, and subsequent to this study's completion the package inserts for both EA and DA were altered to recommend dose reduction or treatment cessation in patients with rapid Hb increment because of concerns about the potential for increased risk of thrombosis [8]. Other label changes included recommendation not to exceed a Hb of 12 g/ dL, and although the label had not yet been revised at the time this protocol was initiated, the treatment guidelines in this study protocol were consistent with that recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, paclitaxel carboplatin regimen intake for 6 cycles in cervical cancer patients would cause Grade 3 anemia with the percentage of 48.3% [20]. Not to mention, a research by El-Deen et al also showed that 6 of 50 ovarium cancer patients who took paclitaxel carboplatin regimen suffered from severe anemia and 32 patients suffered from mild anemia [21].…”
Section: Difference In Blood Function Toxicitymentioning
confidence: 99%